Do Medical Treatments Work for Work? Evidence from Breast Cancer Patients - N. Meltem Daysal; William N. Evans; Mikkel Hasse Pedersen; Mircea Trandafir (Center for Economic Studies and ifo Institute (CESifo), 2024)
We investigate the effects of radiation therapy on the mortality and economic outcomes of breast cancer patients. We implement a 2SLS strategy within a difference-in-difference framework exploiting variation in treatment stemming from a medical guideline change in Denmark. Using administrative data, we reproduce results from an RCT showing the lifesaving benefits of radiotherapy. We then show therapy also has economic returns: ten years after diagnosis, treatment increases employment by 37% and earnings by 45%. Mortality and economic results are driven by results for more educated women, indicating that equalizing access to treatment may not be sufficient to reduce health inequalities.
Keywords: I10; I14; I18; J20; 330; breast cancer; medical treatments; employment; mortality